REPELLENCY OF LOCAL DIATOMACEOUS EARTH ON WHEAT AGAINST SOME COLEOPTERAN STORED-PRODUCT PESTS - Ali Bayram; Ali Arda ISIKBER (Journal of Animal and Plant Sciences, 2025)
In this study, the repellent effect of a local diatomaceous earth (DE) formulation (Demite®) was evaluated on monolayer and bulk wheat against three coleopteran stored-grain pests: the lesser grain borer (Rhyzopertha dominica (Fabricius), Coleoptera: Bostrichidae), the confused flour beetle (Tribolium confusum Jacquelin du Val, Coleoptera: Tenebrionidae), and the rice weevil (Sitophilus oryzae (L.), Coleoptera: Curculionidae) Two-choice tests were conducted to assess insect behavior on treated and untreated surfaces at a DE concentration of 1000 ppm. The experiments measured insect preferences on monolayer wheat surfaces and within bulk wheat at specific observation intervals. The repellency tests were performed under controlled conditions: 25 ± 1 °C temperature, 65 ± 5% relative humidity, and complete darkness in an insect growth room. The repellency of Demite® significantly varied between application methods. On monolayer wheat, the strongest response was observed for T. confusum (97%), followed by S. oryzae (72%) and R. dominica (56%). In contrast, bulk wheat tests showed higher repellency for S. oryzae (90%) and T. confusum (89.3%), while R. dominica exhibited lower responsiveness (53.3%). Significant differences in repellency among the insect species were detected. Sitophilus oryzae and T. confusum exhibited strong repellency across all observation periods, whereas R. dominica was less affected by DE-treated wheat. In conclusion, the local DE formulation demonstrated notable repellent properties, making it a valuable tool in stored grain pest control strategies.
Keywords: Demite®; Integrated pest management; Monolayer wheat; Repellent effect; Two-choice tests